Nursing diagnosis of delayed surgical recovery - Rosimere Ferreira Santana; Tallita Mello Delphino; Nathalia Martins Henriques; Priscilla Alfradique de Souza; Thais da Silva Soares; Shimmenes Kamacael Pereira (Rev Rene)
The purpose of this study was to identify and analyze the nursing diagnosis of delayed surgical recovery, its defining characteristics and related factors according to NANDA-I taxonomy, through an integrative review. 34 articles were selected from MEDLINE, CINAHL, LILACS, and BDENF databases. In these, the delayed surgical recovery diagnosis was identified in a study. However, it was possible to identify the defining characteristics: difficulty to move about (36.4%) which requires help to complete self-care (27.3%) and the evidence of interrupted healing of the surgical site (27.3%). Additionally, the related factors were: pain (34.2%), postoperative surgical site infection (31.7%), postoperative expectations (31.7%), and obesity (2.4%). Other identified related factors were: advanced age (38.9%), diabetes mellitus (22.2%) and nutritional deficiency (16.7%). In conclusion, the diagnosis deals with a phenomenon of nursing surgical practice, recommended for the monitoring and standardized documentation of complications that may delay recovery and hospital discharge.